2021
DOI: 10.51574/kognitif.v1i1.12
|View full text |Cite
|
Sign up to set email alerts
|

Kecemasan Siswa Sekolah Menegah Atas dalam Menyelesaikan Masalah pada Materi Program Linier dalam Praktek Kelas Virtual

Abstract: Pembelajaran matematika secara virtual telah mengubah bagaimana siswa merespons situasi belajar dan tidak jarang meningkatkan kecemasan siswa. Tujuan dari penelitian ini mengungkapkan secara deskriptif bagaimana kecemasan yang terjadi pada siswa pada saat mempelajari program linear dalam pembelajaran matematika secara virtual. Metode penelitian ini menggunakan metode kuantitatif dengan menggunakan survey secara online agar dapat menjangkau seluruh subjek penelitian. Analisis data penelitian dideskripsikan seca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(52 reference statements)
0
3
0
1
Order By: Relevance
“…Meanwhile, when lectures are only run asynchronously, students will find it difficult to ask questions or discuss if there is still material that has not been understood, and it is challenging to control less disciplined students. Similar to these findings, asynchronous learning creates a lack of interaction with fellow students so that if students do not understand the material taught by the teacher, students may experience a lack of interest and enthusiasm for learning (Febryliani et al, 2021).…”
Section: Synchronous and Asynchronous Lecturesmentioning
confidence: 67%
“…Meanwhile, when lectures are only run asynchronously, students will find it difficult to ask questions or discuss if there is still material that has not been understood, and it is challenging to control less disciplined students. Similar to these findings, asynchronous learning creates a lack of interaction with fellow students so that if students do not understand the material taught by the teacher, students may experience a lack of interest and enthusiasm for learning (Febryliani et al, 2021).…”
Section: Synchronous and Asynchronous Lecturesmentioning
confidence: 67%
“…Based on the finding that the average percentage obtained is 66%, it can be interpreted that there is a tendency that students experience learning difficulties in several aspects of themselves. This can be caused by various factors, such as lack of motivation, anxiety, or personal problems experienced by students (Febryliani et al, 2021). In addition, from the diagram of learning difficulties in aspects of children's self, it is found that most students are classified as having learning difficulties.…”
Section: Resultsmentioning
confidence: 99%
“…Tingkat kreativitas kreatif siswa ditentukan oleh hasil berpikir kreatif yang dihasilkan dalam setiap penemuan baru, ide, dan bukan hanya sebatas menghasilkan sesuatu yang bermanfaat saja. Kreativitas dalam berpikir sangat berpengaruh terhadap proses pembelajaran (Suherman, 2015, Febryliani et. al, 2021.…”
Section: Introductionunclassified